PERBAIKAN MANAJEMEN PAKAN PADA PETERNAK BABI DI BENTENG KARANG DUSUN AMA ORY DESA PASSO KECAMATAN TELUK AMBON BAGUALA - Ralahalu, Tabita Naomi; Malle, Dominggus; Hehanussa, Christine H (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Raising pigs in the Benteng Karang community is one of the efforts to increase income. The purpose of this community service activity is to add insight into raising pigs, especially in terms of improving feed management, besides that breeders can use the application of feed technology in the form of processing food crop waste to be used as animal feed. The implementation method used in community service activities is to make an initial approach with the Chairperson of the Benteng Karang Congregational Assembly and the heads of the partner groups. Implementation of community service in the form of counseling, and questions and answers about various practical knowledge related to pig feed improvement management. Apart from that, leaflets were distributed as information material about feed ingredients, nutritional needs according to the age of livestock and processing of restaurant waste. The presentation of the material “improving pig feed management”, received serious attention from breeders. Community service activities carried out at the Benteng Karang of Ama Ory Hamlet, Passo Village in a group of pig breeders partners increased farmers knowledge about improving feed management